2012
DOI: 10.1074/jbc.m111.266007
|View full text |Cite
|
Sign up to set email alerts
|

Detailed Structural-Functional Analysis of the Krüppel-like Factor 16 (KLF16) Transcription Factor Reveals Novel Mechanisms for Silencing Sp/KLF Sites Involved in Metabolism and Endocrinology

Abstract: Background: KLF16 is the least characterized family member of recently described metabolic regulators.Results: We extensively characterize mechanisms of DNA binding and chromatin coupling used by KLF16 to regulate metabolic gene expression.Conclusion: KLF16 is a novel regulator of metabolic genes by regulatable coupling to Sin3-histone deacetylase complexes.Significance: This knowledge reveals key mechanisms used by KLF16 as a regulator of metabolic gene expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 50 publications
(80 reference statements)
0
46
0
Order By: Relevance
“…One would expect the Sin3-mediated mechanism to be inactivated in order for KLF10 to express PCAF-induced activation. Inactivation may occur through KLF10 posttranslational modifications downstream of lymphocyte cell signaling cascades in a similar manner to Sin3-binding disruption to KLF11 (12) and KLF16 (8).…”
Section: Epigenetic Regulation Of Foxp3mentioning
confidence: 99%
See 2 more Smart Citations
“…One would expect the Sin3-mediated mechanism to be inactivated in order for KLF10 to express PCAF-induced activation. Inactivation may occur through KLF10 posttranslational modifications downstream of lymphocyte cell signaling cascades in a similar manner to Sin3-binding disruption to KLF11 (12) and KLF16 (8).…”
Section: Epigenetic Regulation Of Foxp3mentioning
confidence: 99%
“…Several key pieces of data are important to consider within the context of this report. First, the SID of the closely related family member KLF16 bears a tyrosine residue (Y10) that is a Src-family tyrosine kinase target and upon which phosphorylation clearly regulates function (8). Second, ERK-induced phosphorylation of KLF11, the most closely related family member to KLF10, has been clearly demonstrated to disrupt Sin3 binding and repressor function (11).…”
Section: Epigenetic Regulation Of Foxp3mentioning
confidence: 99%
See 1 more Smart Citation
“…1) that contains a CtBP recognition motif (Lahiri and Zhao, 2012;Schuierer et al, 2001;Turner and Crossley, 1998;van Vliet et al, 2000), and KLF9, 10, 11, 13, 14 and 16 contain a Cabut domain in their N-terminal section ( Fig. 1) that encompasses a Sin3 interaction domain (SID) and is referred to as a transcriptional regulatory repression domain (Cook et al, 1999;Daftary et al, 2012;Kaczynski et al, 2001Kaczynski et al, , 2002Lomberk et al, 2013;Truty et al, 2009;Zhang et al, 2001a). Nuclear localization signals (NLSs) have also been identified in several KLFs (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that growth factors functionally modulate KLFs by triggering posttranslational modification or cytoplasm-to-nucleus shuttling of KLFs (Lomberk and Urrutia, 2005;Daftary et al, 2012). For example, the phosphorylation of KLF16 (one of the KLF family members) modulates its transcriptional activity assessed by reporter gene expression, and certain serum factors have been shown to significantly decrease the nuclear translocation of KLF16 and its transcriptional activity (Daftary et al, 2012).…”
Section: Discussionmentioning
confidence: 99%